Yogurt Supplementation In Rats (Rattus Norvegicus) Foods Affected by Formaldehyde Exposure to Enzymatic Antioxidant Activity at Hepar tissue - Chanif Mahdi; Aulanniam Aulanniam (Natural B, Journal of Health and Environmental Sciences, 2011)
Yogurt or yogurt is fermented milk products are rich in various vitamins and amino acids, has potential as a potential source of exogenous antioxidants. Formaldehyde is an organic compound or the aldehyde group of the most simple alkanal are toxic and carcinogenic, presenting in the body can act as a source of compounds reactive oxygen species (ROS) and free radicals that damage cells and tissues are organs. The purpose of this study was to determine the effects of formaldehyde as a toxic compound, and yogurt as detoksikan of antioxidant activity in this regard is the enzymatic antioxidant activity superoksid dismutase (SOD) and levels of reduced glutathione (GSH). The results showed that exposure to various doses of formaldehyde in food rat (Rattus norvegicus) respectively is 0 ppm, 25 ppm 50 ppm 75 ppm and 100 ppm is very real effect (P <0.01) toward decreased antioxidant enzymatic activity in this regard is the reduction of activity superoksid dismutase (SOD) and GSH levels).The results also showed that treatment of yogurt supplementation at 2 ml per cow per day in rats (Rattus norvegicus) were exposed to formaldehyde are not able to change the effect of formaldehyde exposure to the decrease of antioxidant activity (SOD activity and GSH levels) with the significance level remains highly significant (P <0.01)